El apellido Moreno y la burla de los linajes - Moreno Hernández, Carlos (El Colegio de México, 2019)
The paper first makes some remarks about the surname Moreno and itsserious-humorous adscription to different characters in Don Quixote and in Quevedoin connection with the so called “burla de los linajes” (mockery of noble descent), the etymology of the surname and the purchase and sale of titles and honors. All this is then brought to bear on the characters of Galdós who have the same surname in Fortunata and Jacinta (1886-1887) and Misericordia (1897), in an attempt to explain the presence and relevance of the same kind of mockery in a different context.